Impact of Job Burnout on Satisfaction and Turnover Intention: Do Generational Differences Matter? - Lu, A.; Gursoy, D (SAGE, 2013)
This study examines possible moderating effects of generational differences (Baby Boomers, Generation X, Millennials) on the relationship between job burnout (emotional exhaustion, cynicism, reduced professional efficacy) and employee satisfaction and turnover intention, as well as its moderating effects on the relationship between employee satisfaction and turnover intention using data collected from employees of a midscale chain hotel. Findings indicate that generational differences between Baby Boomers and Millennials have significant moderating effects on the relationship between emotional exhaustion and job satisfaction and turnover intention, and on the relationship between job satisfaction and turnover intention.